2022
DOI: 10.1108/jpbm-11-2021-3721
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived risk influence the intention to purchase second-hand clothing? A multigroup analysis of SHC consumers versus non-SHC consumers

Abstract: Purpose This study aims to investigate the influence of perceived risk, including financial, functional, aesthetic, sanitary, psychological and social risks, on the intention to purchase second-hand clothing (SHC) between SHC consumers and non-SHC consumers based on perceived risk theory. Design/methodology/approach A total of 290 responses were collected, with 110 from SHC consumers and 180 from non-SHC consumers. Partial least squares structural equation modelling was used to validate the hypotheses. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…, 2023; Yang and Lee, 2022). Specifically, cleaning of clothing on secondhand clothing-sharing platforms has emerged as significant negative factors that affect consumer attitude when using the platforms (Koay et al. , 2023; Xu et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2023; Yang and Lee, 2022). Specifically, cleaning of clothing on secondhand clothing-sharing platforms has emerged as significant negative factors that affect consumer attitude when using the platforms (Koay et al. , 2023; Xu et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…B2C companies typically take responsibility for these processes, whereas C2C platforms largely leave them to sellers (Kim and Jin, 2021). The concerns regarding sanitation have been shown to influence consumer's adoption of secondhand clothing and shared services (Koay et al, 2023;Yang and Lee, 2022). Specifically, cleaning of clothing on secondhand clothing-sharing platforms has emerged as significant…”
Section: Consumer Contamination Effect and The Influence Of Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Financial risk is widely recognised as the most significant factor among other risk factors that influence consumers’ decision-making processes (Quan et al , 2022). Several studies found that financial risk plays a determining role in consumers’ purchase decisions (Pillai et al , 2022; Koay et al , 2023a). Moreover, the impact of a specific risk on consumers’ behavioural intentions could be enhanced in the presence of other types of risk (Koay et al , 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that financial risk plays a determining role in consumers’ purchase decisions (Pillai et al , 2022; Koay et al , 2023a). Moreover, the impact of a specific risk on consumers’ behavioural intentions could be enhanced in the presence of other types of risk (Koay et al , 2023b). Thus, it is argued that financial risk alone may not be sufficient to deter consumers from engaging in digital piracy because the benefits may outweigh the negative consequences.…”
Section: Introductionmentioning
confidence: 99%